Empirical analysis of mass flow and operation performance of a full-scale biogas plant for human feces treatment - Duojiao, Zhang; Na, Duan; Cong, Lin; Yilin, Zhang; Qiuzi, Xu; Zhidan, Liu (International Journal of Agricultural and Biological Engineering, 2017)
With the rapid development of urbanization in China, the existing municipal network cannot cover all areas and solve all human waste treatment problems. Biogas plants, as an important nationally developmental strategy for cleaner energy production and environmental protection, have been widely used in many industrial and agricultural fields. This research analyzed the mass flow and operation performance in a biogas plant treating human feces at a practical rather than laboratory scale. The biogas plant operated on mesophilic semi-continuous mode at the organic loading rates (OLRs) of 0.56 kg volatile solid (VS)/(m³·d) and average total solid (TS) contents of 3.50%. Results showed that the average biogas production and methane yield were (145±10) m³/d and (471±17) m³ CH4/(t VS), respectively. Annual total feeding amount was 2555.0 t. Among these, there were 58.04 t biogas and 2496.97 t digestate, including 43.07 t solid residues and 2453.90 t liquid digestate. For the full-scale biogas plant, anaerobic bacteria could acclimatize to high total ammonia nitrogen (TAN) concentration (3659 mg/L) and tolerate high free ammonia nitrogen (FAN) concentration of 561 mg/L. It also had strong autoregulation for adapting the large range (2.02-15.18 g/L) and high concentration (15.18 g/L) of influent volatile fatty acid (VFA). In order to achieve its sustainable development and high efficient operation, it is very important to improve the feeding concentration, using digestate to dilute raw material and adding some high C/N raw material in human feces. In conclusion, the biogas plant was an excellent alternative technology for treating human feces.Keywords: biogas plant, human feces, mass flow, operation performance, methaneDOI: 10.3965/j.ijabe.20171002.2703Citation: Zhang D J, Duan N, Lin C, Zhang Y L, Xu Q Z, Liu Z D. Empirical analysis of mass flow and operation performance of a full-scale biogas plant for human feces treatment. Int J Agric & Biol Eng, 2017; 10(2): 233–241.